PENGEMBANGAN APLIKASI MOBILE LEARNING PADA MATERI STRUKTUR ORGANEL SEL UNTUK HASIL BELAJAR SMAN1 PEMATANGSIANTAR - Purba, Melfa Uli Magdalena; Situmorang, Masni Veronika; Silalahi, Mastiur Verawaty (Smart Education, 2025)
Abstract: Mobile learning is a study device for that utilizes technology and mobile gadget . The term M-Learning refers to the utilization of portable or handheld devices. Based on the findings from observations at SMA Negeri 1 Pematangsiantar, information on the use of media was obtained that was still lacking, making students less likely to capture learning in class, thus making student learning outcomes decrease. There are around 165 students who graduated or completed 38.14% and there are 267 people who did not complete or 61.86% of students who did the objective of this study is to evaluate thr viability of developing mobile learning applications on cell organelle structure materials for learning outcomes. To identify the students reactions to the use of mobile learning application development on cell organelle structure material and to determine student learning achievements following implementing the development of mobile learning applications to improve learning outcomes in cell organelle structure material. This (R&D) methods with the use ADDIE model. The findings from the feasibility assessment of the mobile learning application by expert validators were obtained on average 95%, which means that the mobile learning application is very appropriate for implementation in the learning process in the classroom. The learning outcomes of students who use mobile learning applications have increased. Student responses to mobile learning applications received a percentage of 91% with the very good category.Keyword: Mobile learning, cell organelle structure, developmentAbstrak: Mobile learning merupakan sebuah perangkat pembelajaran yang menggunakan teknologi dan perangkat mobile. Kata M-Learning maupun mengacu pada pemakaian perangkat genggam. Dari perolehan pengamatan di SMA Negeri 1 Pematangsiantar mendapat keterangan bahwa penggunaan media yang masih kurang sehingga membuat para peserta didik kurang dalam menangkap pembelajaran dikelas sehingga membuat hasil belajar peserta didik menurun. Siswa yang lulus atau tuntas sekitar 165 orang atau 38,14 % dan terdapat 267 orang yang tidak tuntas atau 61,86 % peserta didik yang tidak tuntas. Studi ini memiliki tujuan untuk melihat kelayakan pengembangan aplikasi mobile learning pada materi struktur organel sel terhadap hasil belajar. Untuk mengetahui respon siswa terhadap penggunaan pengembangan aplikasi mobile learning pada materi struktur organel sel serta untuk mengetahui hasil belajar siswa setelah menerapkan pengembangan aplikasi mobile learning untuk meningkatkan hasil belajar pada materi struktur organel sel. Penelitian ini menggunakan metode (R&D) dengan menggunakan model ADDIE. Hasil uji kelayakan aplikasi mobile learning oleh validator ahli diperoleh rata-rata 95% yang berarti aplikasi mobile learning sangat layak digunakan dalam proses pembelajaran di kelas. Hasil belajar siswa yang menggunakan aplikasi mobile learning mengalami peningkatan. respon siswa terhadap aplikasi mobile learning mendapat persentase 91 % dengan kategori sangat baik.Kata kunci: Mobile learning, struktur organel sel, pengembangan